REBT Counseling for Indonesian Diaspora Junior High School Students from Arab Indonesian Multicultural Families at Sekolah Indonesia Jeddah - Reri Saputra; Kamalatan Nihaya (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2025)
This study explores the application of Rational Emotive Behavioral Therapy (REBT) in addressing the fear of speaking Indonesian among two Indonesian diaspora junior high school students from Arab Indonesian multicultural families at Sekolah Indonesia Jeddah. The problem examined in this study is not merely related to linguistic ability, but rather to psychological factors, particularly feelings of shame and fear of being mocked, which are rooted in irrational beliefs about social evaluation. This study aims to describe the process and outcomes of REBT counseling in modifying students’ irrational beliefs, emotional responses, and speaking behaviors. A qualitative approach with a multiple case study design was employed. Data were collected through in-depth interviews, observation of counseling sessions, and documentation of counseling records. The counseling process was conducted through pre-intervention assessment, REBT-based intervention using the ABCDE model, and post-intervention evaluation. The findings indicate that REBT counseling facilitated meaningful changes in students’ cognitive and emotional patterns, marked by increased emotional awareness, a shift from reactive to reflective emotional responses, and the development of more adaptive beliefs toward speaking Indonesian. These cognitive and emotional changes were followed by behavioral improvements, as students gradually demonstrated greater confidence and willingness to communicate in Indonesian. The study concludes that REBT is an effective counseling approach for addressing language-related social anxiety in multicultural school settings and highlights its practical relevance for guidance and counseling services in Indonesian schools abroad.